(untitled) (International Journal of Engineering and Computer Science, 2015)
Slurry infiltrated fibrous concrete (SIFCON) is a novel type of high performance fibre reinforced concrete made by infiltrating steel fibre bed with a specially designed cement based slurry. Laboratory experiments have shown that SIFCON is an innovative construction material possessing both high strength and large ductility. In the present study, the use of SIFCON has been investigated as an externally bonded strengthening material on reinforced concrete beams The experimental programme has been carried out to study the behaviour of flexural RC beams with precast SIFCON laminates. A total number of twenty one specimens of size 150mm x 300mm x1800mm corresponding to four test series are cast and tested under static loading to study the load deformation behaviour and ductility associated parameters. The concrete beams has been designed to obtain a concrete grade of M20.For laminates the fibre volume fraction was 7% and 10%. The steel fibres used in the study were hooked end steel fibres having 0.6mm diameter and aspect ratio of 50. Previous results indicate that the strengthening of RC beams with SIFCON laminates has significantly improved the cracking behaviour in terms of significant increase in first crack load and the formation of larger number of finer cracks. The stiffness, ductility and energy absorption are found to be increase to a great extent when the beams are strengthened by three face confinement ( bottom & side faces ).